The Challenges of Secondary Education Digitization from the Teachers' Perspective- A Field Study in Secondary Schools in M'sila. - djaalab, Nourdine; saoudi, Ahmed (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
Throughout this study, we have discussed the issue of digitization in the education sector, which is one of the important topics that has imposed itself on theorists, researchers, and practitioners alike for its paramount significance in facilitating and managing the teaching and learning process especially in the light of the information revolution that influenced all areas of daily life. We have focused in this study on the most important challenges that face the digitization of the learning process and its requirements such as logistic, informational, educational, and pedagogical arrangement, in particular in secondary education considering that it is the final stage in the educational trajectory before accessing higher education and then the world of labor. We have chosen some of the secondary schools in the state of M’sila as a study field. With regard to the type of the study, we have relied on the descriptive approach, through applying a questionnaire prepared by the researchers, depending on the theoretical legacy and the basics of the specialty and some previous studies. This questionnaire was rationed and then applied on an arbitrary sample of sixty secondary education teachers working on the level of some of the secondary schools in the state of M’sila. After data was gathered and processed using a set of statistical methods, we attained a group of results in the form of the existence of some challenges, of medium, high, and low intensity facing the digitization of the learning process in secondary education stage, and related to the media, the teacher, the curriculum, the administration, and the student.